2023
DOI: 10.1002/pro.4684
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of affinity between p53 transactivation domain and MDM2 across the animal kingdom demonstrates high plasticity of motif‐mediated interactions

Abstract: The interaction between the transcription factor p53 and the ubiquitin ligase MDM2 results in the degradation of p53 and is well-studied in cancer biology and drug development. Available sequence data suggest that both p53 and MDM2-family proteins are present across the animal kingdom. However, the interacting regions are missing in some animal groups, and it is not clear whether MDM2 interacts with, and regulates p53 in all species. We used phylogenetic analyses and biophysical measurements to examine the evo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…The previous reconstruction of the p53TAD canonical binding motif from the common ancestor of fishes/tetrapods ( Mihalič et al 2023 ) suggested the presence of all three hydrophobic residues (in bold) that point into the binding pocket and make interactions with MDM2 in human p53TAD: S 15 Q 16 E 17 T 18 F 19 S 20 D 21 L 22 W 23 K 24 L 25 L 26 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…The previous reconstruction of the p53TAD canonical binding motif from the common ancestor of fishes/tetrapods ( Mihalič et al 2023 ) suggested the presence of all three hydrophobic residues (in bold) that point into the binding pocket and make interactions with MDM2 in human p53TAD: S 15 Q 16 E 17 T 18 F 19 S 20 D 21 L 22 W 23 K 24 L 25 L 26 ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 90%
“…See Table 1 and supplementary table S1, Supplementary Material online for errors. The affinity at the node representing the divergence of fishes and tetrapods, marked with a star, was determined previously ( Mihalič et al 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations